Metadherin, p50, and p65 Expression in Epithelial Ovarian Neoplasms: An Immunohistochemical Study. (22nd May 2014) - Giopanou, Ioanna; Bravou, Vasiliki; Papanastasopoulos, Panagiotis; Lilis, Ioannis; Aroukatos, Panagiotis; Papachristou, Dionysios; Kounelis, Sophia; Papadaki, Helen
Abstract : NF- κ B signaling promotes cancer progression in a large number of malignancies. Metadherin, a coactivator of the NF- κ B transcription complex, was recently identified to regulate different signaling pathways that are closely related to cancer. We assessed the immunohistochemical expression of p50, p65, and metadherin in 30 ovarian carcinomas, 15 borderline ovarian tumours, and 31 benign ovarian cystadenomas. Ovarian carcinomas exhibited significantly higher expression of all 3 markers compared to benign ovarian tumours. Borderline ovarian tumours demonstrated significantly higher expression for all 3 markers compared to benign cystadenomas. Ovarian carcinomas demonstrated significantly higher expression of p50 and metadherin compared to borderline ovarian tumours, whereas no significant difference was noted in p65 expression between ovarian carcinomas and borderline ovarian tumours. There was a strong correlation with the expression levels of p50, p65, and metadherin, whereas no correlation was observed with either grade or stage. Strong p50, p65, and metadherin expression was associated with a high probability to distinguish ovarian carcinomas over borderline and benign ovarian tumours, as well as borderline ovarian tumours over benign ovarian neoplasms. A gradual increase in the expression of these molecules is noted when moving across the spectrum of ovarian carcinogenesis, from borderline ovarian tumours to epithelial carcinomas.